Sulettaria meekiongii, A new Zingiberaceae species from western Sarawak, Borneo - Ripen, Jovita Elderson; Teo, Stephan Ping; Meekiong, Kalu (Gupta Publications, 2023)
Sulettaria meekiongii Ripen & S.P. Teo, a new Zingiberaceae species is described herein. The new species is close to Sulettaria polycarpa. The new species can be differentiated by the pure white flower and fruits enclosed by the bract, (vs S. polycarpa) flower is white with a yellow band at the median of the labellum and the fruits are exposed. With the discovery of the new species, the number of Sulettaria species in Sarawak now has increased to 14 species. Keywords: species, Sarawak, Borneo, zingiberaceae